Neurogenic Heterotopic Ossifications Recapitulate Hematopoietic Stem Cell Niche Development Within an Adult Osteogenic Muscle Environment - Girard, Dorothée; Torossian, Frédéric; Oberlin, Estelle; Alexander, Kylie A.; Gueguen, Jules; Tseng, Hsu-Wen; Genêt, François; Lataillade, Jean-Jacques; Salga, Marjorie; Levesque, Jean-Pierre; Le Bousse-Kerdilès, Marie-Caroline; Banzet, Sébastien (Frontiers in Cell and Developmental Biology, 2021)
Hematopoiesis and bone interact in various developmental and pathological processes. Neurogenic heterotopic ossifications (NHO) are the formation of ectopic hematopoietic bones in peri-articular muscles that develop following severe lesions of the central nervous system such as traumatic cerebral or spinal injuries or strokes. This review will focus on the hematopoietic facet of NHO. The characterization of NHO demonstrates the presence of hematopoietic marrow in which quiescent hematopoietic stem cells (HSC) are maintained by a functional stromal microenvironment, thus documenting that NHOs are neo-formed ectopic HSC niches. Similarly to adult bone marrow, the NHO permissive environment supports HSC maintenance, proliferation and differentiation through bidirectional signaling with mesenchymal stromal cells and endothelial cells, involving cell adhesion molecules, membrane-bound growth factors, hormones, and secreted matrix proteins. The participation of the nervous system, macrophages and inflammatory cytokines including oncostatin M and transforming growth factor (TGF)-β in this process, reveals how neural circuitry fine-tunes the inflammatory response to generate hematopoietic bones in injured muscles. The localization of NHOs in the peri-articular muscle environment also suggests a role of muscle mesenchymal cells and bone metabolism in development of hematopoiesis in adults. Little is known about the establishment of bone marrow niches and the regulation of HSC cycling during fetal development. Similarities between NHO and development of fetal bones make NHOs an interesting model to study the establishment of bone marrow hematopoiesis during development. Conversely, identification of stage-specific factors that specify HSC developmental state during fetal bone development will give more mechanistic insights into NHO.